Single_Crystal_to_Single_Crystal Installation of Ln4(OH)4 Cubanes in an Anionic Metallosupramolecular Framework - Nobuto Yoshinari; Natthaya Meundaeng; Hiroyasu Tabe; Yusuke Yamada; Satoshi Yamashita; Yasuhiro Nakazawa; Takumi Konno (My University, 2020)
Abstract Postsynthetic installation of lanthanide cubanes into a metallosupramolecular framework via a single‐crystal‐to‐single‐crystal (SCSC) transformation is presented. Soaking single crystals of K 6 [Rh 4 Zn 4 O( l ‐cys) 12 ] (K 6 [ 1 ]; l ‐H 2 cys= l ‐cysteine) in a water/ethanol solution containing Ln(OAc) 3 (Ln 3+ =lanthanide ion) results in the exchange of K + by Ln 3+ with retention of the single crystallinity, producing Ln 2 [ 1 ] ( 2 Ln ) and Ln 0.33 [Ln 4 (OH) 4 (OAc) 3 (H 2 O) 7 ][ 1 ] ( 3 Ln ) for early and late lanthanides, respectively. While the Ln 3+ ions in 2 Ln exist as disordered aqua species, those in 3 Ln form ordered hydroxide‐bridged cubane clusters that connect [ 1 ] 6− anions in a 3D metal‐organic framework through coordination bonds with carboxylate groups. This study shows the utility of an anionic metallosupramolecular framework with carboxylate groups for the creation of a series of metal cubanes that have great potential for various applications, such as magnetic materials and heterogeneous catalysts.
Keywords: Carboxylate; Cubane; Crystal (programming language); Magnetism in coordination complexes